Advances in Testosterone Action - Estrada, Manuel (IntechOpen, 2018)
This book describes recent findings on androgens. The chapters include information on physiological and pathological conditions such as alteration in testosterone production by Leydig cells, prostate cancer, and metabolic disorders. Moreover, this book refers to the potential use of androgens in assisted human reproduction treatments and bovine breeding. Since each chapter contains background information based on evidence and emphasizes basic science, this book is aimed at professionals who already have a basic understanding of the principles of androgen biochemistry and endocrine-related diseases.